Graffiti as an agent for effecting sexual behavioral change among female students in Zimbabwe's high schools - Mangeya, Hugh (University of Zimbabwe Publications, 2018)
This chapter analyzes graffiti as a product of social constructionism in which members are actively involved in creating a reality to which only they can identify with. It also makes the argument that this social construction of reality is done within a framework in which power dynamics take centre stage.